Erfahrung, Lernen, Metapher.: Aspekte einer angewandten Metaphorologie, dargestellt am Beispiel von Raum- und Zeitmetaphern im Instrumentalunterricht - Agnetta, Marco (Linguistik Online, 2026)
The present article examines how the use of similes and metaphors, especially those relating to spatial and temporal concepts, can build, activate and modify knowledge in an instructional context. Music teachers consciously and unconsciously make use of the ability of linguistic images to support learning. On the basis of findings from Cognitive Metaphor Theory (cf. Lakoff/Johnson (1980), which is presented here as a theory of human experience, it will be shown to what extent music instruction regularly leads to situations in which the teacher’s experiential knowledge, internalized over many years, is brought up and negotiated with the pupil. Questions relating to the learnability of virtuous skills (Plato) and the passing on of experiential knowledge in a dialogically oriented situation (Buber) play a prominent role here. Specifically, using the example of a series of online music tutorials on playing the viola da gamba, it is shown that experiential knowledge is verbalized via a dense network of different communicative strategies. This consists of (spatio-temporal) comparisons, metaphors, non-metaphorical formulations, gestures and pictorial elements. In the multimodal communication situation that music lessons represent, all of these communicative means are geared towards the goal of a change in thinking and behavior for the benefit of the student’s learning progress.